2019
DOI: 10.1021/acs.jpca.9b09113
|View full text |Cite
|
Sign up to set email alerts
|

Conformer Specific Ultraviolet and Infrared Detection of Nicotine in the Vapor Phase

Abstract: A gas-phase electronic spectrum of nicotine in a supersonic expansion has been recorded using two-color resonant two-photon ionization spectroscopy. Efficient photoionization was achievable only via the pyridine chromophore owing to poor Franck−Condon overlap in the N-methylpyrrolidine moiety. Two conformers of nicotine have been characterized and assigned by infrared−ultraviolet (IR−UV) ion depletion and IR−UV hole-burning spectroscopy, in combination with quantum chemical techniques. Trans-A with nitrogen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We considered the enantiomer S of nicotine since it is the one formed naturally; 52 the rate constants of the reaction of the enantiomers R and S with nonchiral species are the same. We found eight distinguishable conformers for nicotine by rotating the dihedrals C1-C2-C6-N2 and N2-C6-C7-C8, which are the pseudorotation within the pyrrolidine ring responsible for its envelope conformation, 53,54 and by changing the orientation of the methyl group bonded to the atom N2, which may display axial or equatorial orientation. All the displayed conformers have been reported in previous works.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We considered the enantiomer S of nicotine since it is the one formed naturally; 52 the rate constants of the reaction of the enantiomers R and S with nonchiral species are the same. We found eight distinguishable conformers for nicotine by rotating the dihedrals C1-C2-C6-N2 and N2-C6-C7-C8, which are the pseudorotation within the pyrrolidine ring responsible for its envelope conformation, 53,54 and by changing the orientation of the methyl group bonded to the atom N2, which may display axial or equatorial orientation. All the displayed conformers have been reported in previous works.…”
Section: Resultsmentioning
confidence: 94%
“…All the displayed conformers have been reported in previous works. 53 −58 Previous experimental and theoretical works pointed out that at room temperature, around 99.9% of nicotine is found in the two lowest-energy conformations, 54 with relative abundance values of 66.3% for the global minimum and 33.4% 57 for the other one. However, at higher temperatures, such as those reached in cigarettes, the higher-energy conformers may become energetically accessible and thus a detailed multistructural study is necessary in order to calculate accurate rate constants.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found multiple conformers for nicotine with respect to the chiral C1 center, the internal rotation around the C1–C1′ bond, and the orientation of the methyl group (axial vs equatorial). , However, the two lowest energy conformers for enantiomer S account for >99.9% of nicotine, and therefore the current study includes only these two conformers. Rotation around the C1–C1′ bond has a barrier of ∼25 kJ/mol (see the energy profiles in Figure S1 for a relaxed scan of dihedral angle), suggesting equilibrium distribution between the two conformers in the reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The data were originally published and made available 1,5 in 2004, and thousands of copies were distributed on a web site, with many of the molecular absorption cross-sections more recently made available as a new product on the HITRAN web site. 8 The spectral data have been used for applications including ambient 9,10 and laboratory monitoring, 11,12 input to radiative transfer models, 13,14 and other endeavors such as atmospheric chemistry, 15,16 gas-phase chemical kinetics, 17,18 combustion science, 19,20 and even fundamental vibrational assignments. 21 Recently, Bernath, Hewett, and co-workers 22−25 have investigated the structure and band strengths of isobutane, C 4 H 10 , for possible monitoring of this species on gas-giant planets such as Jupiter and Saturn as well as the gas-phase composition of their moons such as Saturn's largest, Titan.…”
Section: Introductionmentioning
confidence: 99%
“…The data were originally published and made available , in 2004, and thousands of copies were distributed on a web site, with many of the molecular absorption cross-sections more recently made available as a new product on the HITRAN web site . The spectral data have been used for applications including ambient , and laboratory monitoring, , input to radiative transfer models, , and other endeavors such as atmospheric chemistry, , gas-phase chemical kinetics, , combustion science, , and even fundamental vibrational assignments …”
Section: Introductionmentioning
confidence: 99%